In search of 'low‐hanging fruits' or 'ideal' candidates? Understanding headhunters' candidate search activities. (29th October 2020) - Peltokorpi, Vesa
Abstract: Drawing on theory and research on labour market intermediaries, we interviewed 51 contingency headhunters specialised in foreign subsidiaries in Japan to explore how they search host country national candidates and what factors influence their search activities. The findings suggest that headhunters search candidates through cold calls, personal and shared databases, online job boards and social network sites, and referrals. The findings also suggest that how headhunters search candidates are congruent with the perceived importance of client organisations, search firm size and headhunters' experience. The findings contribute to human resource management research by providing evidence of a complex cost‐benefit and experience‐related candidate search activities.